Rhetorical theory and praxis in the business communication classroom - Getchell, Kristen M.; Lentz, Paula (Routledge, 2019)
"Rhetorical Theory and Praxis in the Business Communication Classroom responds to a significant need in the emerging field of business communication as the first collection of its type to establish a connection between rhetorical theory and practice in the business communication classroom. The volume includes topics such as rhetorical grammar, genre awareness in business communication theory, the role of big data in message strategy, social media and memory, and the connection between rhetorical theory and entrepreneurship. These essays provide the business communication scholar, practitioner, and program administrator insight into the rhetorical considerations of the business communication landscape"--Provided by publisher.